Komunikasi Persuasif Satuan Polisi Pamong Praja Surabaya dalam Menertibkan Penyandang Masalah Kesejahteraan Sosial - Arifah Putri Sabillah; Fitria Widiyani Roosinda (Universitas Medan Area, 2020)
The purpose of this study was to determine the effectiveness of Surabaya City Satpol PP persuasive communication in curbing Persons with Social Welfare Problems. This type of research is descriptive quantitative research, namely research that aims to describe or describe the numbers that have been processed according to certain standards. This descriptive research method was conducted to determine the existence of independent variables, either only in one or more variables (independent variables or independent variables) without making comparisons of the variables themselves and looking for relationships with other variables. The result of this research is the effectiveness of Persuasive Communication of Satpol PP of Surabaya City in controlling PMKS when it reaches 70%, and the results of calculations that have been done are known to reach 84%. So it can be concluded that the persuasive communication of the Surabaya City Satpol PP in curbing Persons with Social Welfare Problems is effective. The conclusion is that the high number of PMKS due to urbanization is not being matched by adequate employment opportunities. The increase in this number also shows that the persuasive communication carried out by the Satpol PP to the community has been successful because of the creation of peace and public order in the surrounding environment. In accordance with the results of the study stated that the level of effectiveness of the Surabaya City Satpol PP persuasive communication in curbing Persons with Social Welfare Problems is effective. It can be seen from the percentage results obtained reaching 84%.